Predictive value of serum neurofilament light chain for cognitive impairment in Parkinson’s disease - Gu, Lihua; Zhang, Pengcheng; Gao, Rui; Shu, Hao; Wang, Pan (Frontiers in Aging Neuroscience, 2024)
BackgroundNeurofilament light chain (NfL) has recently emerged as a key indicator of neurodegeneration. In this study, our hypothesis is that the levels of blood-derived NfL and its accumulation during the Parkinson’s disease (PD) progression could serve as a potential biomarker for predicting subsequent cognitive decline. To investigate this, we conducted a study utilizing a large single-center cohort.MethodsThe study included 193 participants, consisting of 106 cognitively normal PD (PD-CN) patients and 87 normal controls (NC) individuals. Serum NfL concentrations were measured. PD patients were followed up for clinical assessment at an average of 2 ± 0.6 years.ResultsThe serum NfL levels were significantly higher in PD-CN patients compared to NC. PD-CN patients and NC at follow-up time exhibited higher serum NfL levels compared to those at baseline. PD patients with high serum NfL levels were found to have a higher likelihood of transitioning from normal cognition to mild cognitive impairment (MCI) or dementia (Hazard ratio (HR) 1.107, 95% confidence intervals (CI) 1.010–1.213, p = 0.030). The area under the curve (AUC) for PD-CN conversion to MCI or dementia at follow-up time was determined to be 0.684 (95% CI 0.569–0.799).ConclusionIn conclusion, our study found that PD patients have significantly higher levels of serum NfL compared to individuals without PD. Furthermore, serum NfL levels increase as PD progresses and can predict cognitive impairment within a 2-year timeframe. Serum NfL may serve as a feasible, non-invasive biomarker of cognitive progression in PD. However, further studies and functional experiments are needed to validate these findings.